Exploration of Zoo felids in North-East China for the prevalence and molecular identification of Cryptosporidium spp. - Shakeel Hussain; Syed Mohsin Bukhari; Lixin Wang; Nimra Khalid; Zhijun Hou (PeerJ, 2021)
Cryptosporidium spp. is a protozoan having the potential to cause zoonosis in humans and animals. Despite the zoonotic importance of this protozoan parasite, limited data are available about its prevalence in zoo felids in North-Eastern China. Hence, the current study was designed to determine the occurrence and molecular characterization of Cryptosporidium spp. from the fecal samples of captive zoo felids. Fecal samples (N = 244) were collected from different felids from five different zoos of North-Eastern China. 18S rRNA gene was amplified from the genomic DNA using species specific primers in nested polymerase chain reaction (nPCR) and Cryptosporidium parvum and Cryptosporidium spp. was found. The overall prevalence of Cryptosporidium was 9.43% (23/244). The 18S rRNA gene similarity analysis showed that 6 Cryptosporidium isolates were Cryptosporidium parvum and the remaining 17 Cryptosporidium isolates were resembling to a Cryptosporidium spp., which is similar to Cryptosporidium NEV10. Phylogenetic tree was constructed based on 18S rRNA of Cryptosporidium spp. The similarity of Cryptosporidium parvum was with its other isolates in China, India, Iran, Iraq, Turkey, Czech Republic, Spain and USA while Cryptosporidium NEV10 alike had a close relationship with Turkish isolates. In conclusion, Cryptosporidium was prevailing in feline animals of China zoo and zoo officials are directed to consider their control policy as it can be a cause of zoonosis.